Monuments and nation. Kyoto as a symbol of the Japanese spirit during the Meiji period. - Sastre de la Vega, Daniel (Mirai. Estudios Japoneses, 2018)
During the Meiji period the city of Kyoto faced the challenge of competing against the new capital of Tokyo after losing its capital status with the move of the Emperor and its entourage to the Kantō region. One of the strategies used in order to re-launch its activity was the organization of different industrial and civil engineering activities, which transformed the way of life of its citizens. The second strategy, promoted by the city´s cultural and political elites, and fostered by the national policies of building a nation-state, was the symbolic configuration of the city and its surroundings as the spiritual origin of the country: a city which had preserved during several generations the values and ideals that shaped what it meant to be Japanese. The realization of these policies took place, for instance, in the trips to the monuments of the capital by primary and secondary schools. At the same time, it was an education process for the future citizens of the Japanese Empire by helping them establish a collective imaginary of the national past. Travel guides and books on the places not to miss while in the ancient capital would be fairly common during the Taishō period when the city was already the favourite destination for national and foreign visitors, and the image of Kyoto as the repository of the nation was completed.